The effectiveness and safety of tubed and tubeless percutaneous nephrolithotomy types in the treatment of preschool-age pediatric kidney stones - A. Al-Zobaie; R. Aal Toma; F. Al-Waeli (Ukrainian Journal of Nephrology and Dialysis, 2022)
The incidence of kidney stones in children has increased in recent years. Unlike adults, the treatment of pediatric kidney stones is more difficult because of the size of the stones and the high risk of recurrence.The present study aimed to evaluate the management of pediatric kidney stones with percutaneous nephrolithotomy in general and with both types of percutaneous nephrolithotomy (PCNL).Methods. This retrospective cross-sectional study was conducted at Al-Safeer Al-Imam Al-Hussein Hospital from November 1, 2019 to October 31, 2021. A total of 90 children with kidney stones were divided into 45 with tubular PCNL and 45 with tubeless PCNL. The children were followed up for at least six months postoperatively.   Results. After PCNL, only 4 children were not stone-free and no injury was noted, whereas sepsis was noted in only one child. Renal status after PCNL was stable renal function in 97.8% of children and improved renal function in 2.2% of children, while no deterioration of renal function was noted. The characteristics of the children, the characteristics of the surgical procedure (except access), and the results of PCNL were not significantly different among the different types of PCNLConclusion. PCNL in both variants (with and without tubing) is a safe and effective surgical option in the treatment of children with renal stones.